2003
DOI: 10.1046/j.1365-8711.2003.06343.x
|View full text |Cite
|
Sign up to set email alerts
|

Time-series spectroscopy of pulsating sdB stars -- III.Line indices of PG 1605+072

Abstract: We present the detection and analysis of line index variations in the pulsating sdB star PG 1605+072. We have found a strong dependence of line index amplitude on Balmer line order, with high‐order Balmer line amplitudes up to 10 times larger than Hβ. Using a simple model, we have found that the line index may not only be dependent on temperature, as is usually assumed for oscillating stars, but also on surface gravity. This information will provide another set of observables that can be used for mode identifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…1) as the lines are overlapping. O'Toole et al (2003b) have also found a strong dependence of line index amplitude on Balmer line order, with high order Balmer line amplitudes up to 10 times larger than H β due to the fact that the line index may not only be dependent on temperature but also on surface gravity.…”
Section: Computation Of Synthetic Line-profile Variationsmentioning
confidence: 89%
See 3 more Smart Citations
“…1) as the lines are overlapping. O'Toole et al (2003b) have also found a strong dependence of line index amplitude on Balmer line order, with high order Balmer line amplitudes up to 10 times larger than H β due to the fact that the line index may not only be dependent on temperature but also on surface gravity.…”
Section: Computation Of Synthetic Line-profile Variationsmentioning
confidence: 89%
“…If the equivalent width of the given line profile is increasing with increasing temperature this absorption feature will be enhanced, whilst if the equivalent width is decreasing with increasing temperature the absorption feature will be reduced and could become an emission feature. Equivalent width variations of Balmer lines are described by a nonlinear combination of temperature and surface gravity (O'Toole et al 2003a). For hot stars such as sdBs, the change of equivalent width with temperature is negative, so that the equivalent width becomes smaller with increasing temperature and the Balmer lines are becoming shallower as the temperature is increasing and deeper as the temperature is decreasing.…”
Section: Computation Of Synthetic Line-profile Variationsmentioning
confidence: 99%
See 2 more Smart Citations
“…PB 8783 and KPD 1209+4401 (Jeffery & Pollacco 2000), PG 1605+072 (O'Toole et al 2003), PG 1325+101 (Telting & Østensen 2004). Recent highresolution FUSE time-series of three sdBV were presented by Kuassivi et al (2005).…”
Section: Introductionmentioning
confidence: 99%